Implementation of an Optimized Steganography Technique over TCP/IP and Tests Against Well-Known Security Equipment - Tarhda, M.; Gouri, R. E.; Hlou, L. (Engineering, Technology & Applied Science Research, 2018)
Nowadays we are witnessing a total convergence towards a digital world where information is digitized, conveyed and processed using highly developed techniques and tools. The development of broadband networks, including the internet, has made easy the manipulation, transmission and sharing of information. However, new security issues arise and they are particularly related to integrity, confidentiality and traceability of data. Facing this situation, network security has become very important and challenges related to the protection of exchanged data over the internet against unauthorized access and use have increased. In the current work, we propose to implement an optimized steganography technique over TCP/IP protocol [1]. We have also tested it against well-known security equipment using latest versions. We will see that they are inefficient to stop this kind of cover channels. Our work is like an alarm to every IT administrator to change their thinking about data lost prevention (DLP) and exfiltration of sensitive information.